2019
DOI: 10.1371/journal.pone.0216063
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic modulation and baroreflex control in the second trimester of pregnancy: A cross sectional study

Abstract: Purpose The aim is to evaluate and characterize cardiovascular autonomic control and baroreflex function and their response to an orthostatic stressor in the second trimester of pregnancy via time, frequency, information and symbolic analyses. Methods We evaluated 22 women at 18 weeks of pregnancy, labeled as pregnant group (PG) (30.8±4.4 years), and 22 non-pregnant women (29.8±5.4 years), labeled as control group (CG). Electrocardiogram, non-invasive photoplethysmograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…As gestation advances, however, the ANS shifts toward a higher sympathetic and lower parasympathetic tone ( Blake et al, 1979 ; Ekholm et al, 1993 ; Kuo et al, 2000 ; Corrêa et al, 2019 ), especially in supine posture, ( DSilva et al, 2014 ; Kuo et al, 2000 ; Blake et al, 1979 ). This biphasic change in ANS activity in pregnancy may be a result of the competing influences and resultant hemodynamic effects of physiologic volume expansion in the second trimester versus aortocaval compression from the enlarging gravid uterus in the third trimester ( DSilva et al, 2014 ; Kuo et al, 2000 ; Maser et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…As gestation advances, however, the ANS shifts toward a higher sympathetic and lower parasympathetic tone ( Blake et al, 1979 ; Ekholm et al, 1993 ; Kuo et al, 2000 ; Corrêa et al, 2019 ), especially in supine posture, ( DSilva et al, 2014 ; Kuo et al, 2000 ; Blake et al, 1979 ). This biphasic change in ANS activity in pregnancy may be a result of the competing influences and resultant hemodynamic effects of physiologic volume expansion in the second trimester versus aortocaval compression from the enlarging gravid uterus in the third trimester ( DSilva et al, 2014 ; Kuo et al, 2000 ; Maser et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spradley et al ( Spradley, 2019 ) showed that baroreflex sensitivity in healthy pregnant women was not altered, while Garg et al ( Garg et al, 2020 ) reported a decrease in cardiovagal modulation and baroreflex sensitivity towards the end of a healthy pregnancy. Corrêa et al ( Da Silva Corrêa et al, 2019 ) found a decrease in parasympathetic modulation and baroreflex sensitivity of healthy pregnancy at rest but a preserved baroreflex response during posture changes. Usselman et al ( Usselman et al, 2015b ) found maintenance of cardiovagal baroreflex but decreased sympathetic baroreflex gain, indicating that the baroreflex might not be the main mechanism of MSNA modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy affects autonomic responses in multiple ways. Various studies have documented various differences, which are further altered by preeclampsia ( Chaswal et al, 2018 ; da Corrêa et al, 2019 ; Garg et al, 2020 ). Autonomic neuropathy is uncommon but can occur in young women.…”
Section: Autonomic Disordersmentioning
confidence: 99%